Historical roots of political extremism : the effects of Nazi occupation of Italy - Fontana, Nicola (Discussion paper / IZA, 2017)
The Italian civil war and the Nazi occupation of Italy occurred at a critical juncture, just before the birth of a new democracy and when, for the first time in a generation, Italians were choosing political affiliations and forming political identities. In this paper we study how these traumatic events shaped the new political system. We exploit geographic heterogeneity in the intensity and duration of the civil war, and the persistence of the battlefront along the "Gothic line" cutting through Northern-Central Italy. We find that the Communist Party gained votes in the post-war elections where the Nazi occupation and the civil war lasted longer, mainly at the expense of the centrist and catholic parties. This effect persists until the early 1990s. Evidence also suggests that this is due to an effect on political attitudes. Thus, the foreign occupation and the civil war left a lasting legacy of political extremism and polarization on the newborn Italian democracy.